An alternative view of the conditions of the formation of the pre-Neogene bed of the Krukenychi depression - Mykhailovskyi, Ihor; Andreychuk, Mykhailo (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Purpose. The Krukenytsk Depression is considered a deep erosional valley formed at the beginning of the Miocene. A comparison of the pre-Neogene paleo-relief of the northwestern Outer Zone of the Pre-Carpathian Trough with the modern structural plan of the surface of the Grand Canyon carved out of the sedimentary layers of the Colorado Plateau is given. An assumption is made about the erosive nature of the narrow strip of articulation of the Krukenytsk Depression with the hypsometrically uplifted Kosiv-Ugrian Subzone of the Outer Zone of the Pre-Carpathian Trough. Method. Based on comprehensive geological and geophysical studies, the Krukenytsia Depression is presented as a component of the Pre-Neogene erosional system of the Outer Zone of the Precarpathian Trough. The main factor in the formation of discontinuous and plicative faults is considered to be gravitational forces, which is the basis for new views on the formation of hydrocarbon traps in the upper molasses section. The purpose of the study is to identify the influence of Pre-Neogene erosional processes on the formation of paleogeomorphological features of the Pre-Neogene bed of the northeastern marginal part of the Krukenytsia Depression. Results. The Krukenytsia Depression differs from the adjacent Kosiv-Uhersk subzone of the Outer zone of the Precarpathian Depression, primarily, in the depths of the pre-Neogene basement, which became the main factor in the abrupt increase in the thickness of the Miocene complex, represented mainly by terrigenous formations of Badenian-Sarmatian age, which, within the depression, overlap strongly dislocated and metamorphosed Riphean formations with an angular and stratigraphic unconformity. The Mesozoic and Paleozoic complexes in the pre-Neogene basement of the Ukrainian part of the Krukenytsia Depression are absent and appear, gradually rejuvenating the latter only on the steep northeastern slope and within its origin in Poland. According to the existing model, the Krukenytska Depression is represented as a megablock of the autochthonous part of the Precarpathian trough submerged along the Krakovets fault, within which the Miocene Upper Molasses complex with stratigraphic and angular unconformity overlies metamorphosed and dislocated Riphean rocks. Scientific novelty. In the pre-Neogene base of the Outer zone of the Precarpathian trough, the northeastern margin of the Krukenytsia depression is first presented as a steep longitudinal slope of a deep erosional paleovalley, complicated by numerous elements of gravity slides of the Meso-Paleozoic stratum. The dominant role in the formation of the block structure of the studied area is first assigned to the forces of gravity in conjunction with the paleogeomorphological features of the pre-Neogene bed. Practical significance. The obtained data allow us to assess in a new way the conditions for the formation of hydrocarbon traps, both in the Miocene terrigenous complex and in the rocks of the pre-Neogene base of the northeastern marginal part of the Krukenytsia depression in order to conduct more targeted geological exploration work in this area of the Outer zone of the trough.